Cytomegalovirus Infection in Pediatric Renal Transplant Recipients: A Single Center Experience - Mi Jin Kim; Ji Hye You; Hye Ryun Yeh; Jin A Lee; Joo Hoon Lee; Young Seo Park (Korean Society of Pediatric Nephrology, 2017)
Purpose To investigate the frequency, presentation, management, and outcome of cytomegalovirus (CMV) infection in pediatric patients who underwent renal transplantation. Methods We performed a retrospective chart review of 70 patients under the age of 18, who underwent renal transplantation between January 1990 and November 2014. A diagnosis of CMV infection was based on serology, molecular assays, antigenemia assays, and culture. CMV infection was defined as detection of virus and CMV disease was diagnosed when clinical signs and symptoms were present. Results The number of patients with CMV infection was 18 (25.7% of renal transplant recipients). Twelve were male (66.7%), and the mean±standard deviation (SD) age at infection was 13.3±3.9 years. Median time of infection after renal transplantation was 4 months (range 1.0-31.0 months). Pretransplantation CMV status in the infected group was as follows: donor (D)+/recipient (R)+, 11 (61.1%); D+/R-, 7 (38.9%); D-/R+, 0; and D-/R- 0. Nine patients had CMV disease with fever, leukopenia, thrombocytopenia, or organ involvement such as enteritis, hepatitis, and pneumonitis. The age of disease occurrence was 13.1±3.9 years and the median time to disease onset after renal transplantation was 8 months (range 1.0-31.0). Immunosuppressive agents were reduced or discontinued in 14 patients (77.8%), antiviral agents were used in 11 patients (61.1%), and all patients with CMV infection were controlled. Conclusions A quarter of the patients had CMV infection about 4 months after renal transplantation. CMV infection was successfully treated with reduction of immunosuppressants or with antiviral agents.